Conversion of Wasted Oil to Biodiesel Using CaO from Chicken Egg Sheets as a Catalist - Jabborov, Behzod; Syarif, Aida; Yerizam, Muhammad (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This research explores the use of used cooking oil as a primary feedstock in biodiesel production, with the addition of a calcium oxide (CaO) catalyst derived from eggshells. The process begins by filtering the used cooking oil to remove impurities, after which the oil undergoes tests to assess its density, viscosity, acid number, free fatty acid content, and water content. These initial steps are crucial to ensure the quality and readiness of the oil for further processing. Following this, the CaO catalyst is produced from eggshells through an impregnation process, a method that allows the transformation of eggshells into an effective catalyst. The study employs a heterogeneous catalyst system, where the CaO catalyst, characterized by its micro-sized particles, is used in the transesterification process. This approach is chosen as an alternative to the conventional use of homogeneous catalysts, providing potential advantages in terms of reusability and environmental impact. The production of biodiesel is conducted in two main stages: esterification and transesterification. In both stages, the CaO from eggshells is utilized as a catalyst, and the filtered used cooking oil serves as the raw material for biodiesel synthesis. The research identifies the optimal conditions for biodiesel production, which include heating the mixture to a temperature of 900°C, using a CaO catalyst amounting to 1% of the weight of the used cooking oil, and maintaining a reaction time of 60 minutes. Under these conditions, the study achieved a biodiesel yield of 62.17%. This research highlights the effectiveness of using waste materials such as eggshells and used cooking oil in producing biodiesel, offering a sustainable and environmentally friendly alternative to traditional methods.